2010
DOI: 10.1016/j.devcel.2010.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Hdac1 and Hdac2 Act Redundantly to Control p63 and p53 Functions in Epidermal Progenitor Cells

Abstract: Summary Epidermal and hair follicle development from surface ectodermal progenitor cells require coordinated changes in gene expression. Histone deacetylases alter gene expression programs through modification of chromatin and transcription factors. We find that deletion of ectodermal Hdac1 and Hdac2 results in dramatic failure of hair follicle specification and epidermal proliferation and stratification, phenocopying loss of the key ectodermal transcription factor p63. While expression of p63 and its positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
258
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(272 citation statements)
references
References 55 publications
12
258
2
Order By: Relevance
“…DNp63 also cooperates with HDAC1/2 to directly repress p16/INK4a in epidermal keratinocytes, whereas HDAC1/2 independently deacetylate p53 and suppress its ability to induce apoptosis and activate target genes, including p21 (LeBoeuf et al 2010). Conversely, p63 gene expression in epidermal keratinocytes is positively regulated by the histone methyltransferase Setd8, as well as by the DEC1 transcription factor (Driskell et al 2011;Qian et al 2011).…”
Section: Va Botchkarev and Er Floresmentioning
confidence: 98%
See 1 more Smart Citation
“…DNp63 also cooperates with HDAC1/2 to directly repress p16/INK4a in epidermal keratinocytes, whereas HDAC1/2 independently deacetylate p53 and suppress its ability to induce apoptosis and activate target genes, including p21 (LeBoeuf et al 2010). Conversely, p63 gene expression in epidermal keratinocytes is positively regulated by the histone methyltransferase Setd8, as well as by the DEC1 transcription factor (Driskell et al 2011;Qian et al 2011).…”
Section: Va Botchkarev and Er Floresmentioning
confidence: 98%
“…The p63 isoforms play distinct roles in the control of epidermal development; the DNp63 isoforms are much more abundant in the epidermis compared to TAp63, which is strongly expressed in basal epidermal keratinocytes and is markedly down-regulated in the spinous epidermal layer (Laurikkala et al 2006;Romano et al 2009Romano et al , 2012LeBoeuf et al 2010;Shalom-Feuerstein et al 2011). TAp63 is also expressed in response to stresses such as wound healing (Su et al 2009b).…”
Section: The P53 Family and Its Isoformsmentioning
confidence: 99%
“…Indeed, loss-of-function studies in mice provide important insights regarding the compensatory functions of HDAC1 and HDAC2 in regulating cell proliferation, apoptosis, and differentiation in different cell types and tissues. 8,28 Tissue-specific conditional knockout of Hdac1 or Hdac2 alone does not evoke an obvious phenotype in cardiomyocytes, 29 neuron precursors, 30 oligodendrocyte, 31 B cells, 32 embryonic epidermis, 33 and T cells, 34 whereas deletion of both genes results in severe phenotypes in all tissues examined. In contrast, results of other studies support the notion that HDAC1 and HDAC2 have distinct functions.…”
Section: Structure and Complexes Of Mammalian Hdac1 And Hdac2mentioning
confidence: 99%
“…[27][28][29][30][31][32] Recent report showed that HDAC1/2 are present at the promoter regions of DNp63-repressed targets in keratinocytes, indicating a direct requirement for HDAC1/2 in DNp63-mediated repression. 39 Materials and Methods Cells and reagents. TheHNSCC cell line JHU-029 (expressing wild-type p53 and p63) was isolated from primary tissue at the Department of Otolaryngology/ Head and Neck Surgery of the Johns Hopkins University School of Medicine.…”
Section: Discussionmentioning
confidence: 99%